P165 Results of the Northumbria Direct access CXR project. (12th November 2015) - Weatherhead, M
Abstract : Northumbria Healthcare (NHCT) traditionally had a low number of patients presenting with early stage lung cancer leading to low resection rates. In addition a high number of patients presented through the emergency route rather than through target clinics. A local initiative was developed to try to improve the local presentation and diagnosis rates. The Northumbria initiative utilised primary care education, a social marketing project and a direct access CXR project which ran for 12 months. The assessment criteria for direct access CXR were based on NICE guidance and patients meeting these criteria could self-present for a CXR. Is the patient over 50 Has the patient had a chest x-ray in the last 3/52 Has the patient developed a new and persistent cough for more than 3/52 Has the patient had persistent chest pain for more than 3/52 Has the patient had blood in their phlegm Results: Over 12 months 768 CXR examinations were carried out. 751 people presented a cough, 192 with chest pain and 33 with haemoptysis. 18 CT`s were requested due to a suspicious CXR and 52 people had a follow up CXR. 19 of these 70 were reviewed in a chest clinic. 4 lung cancers were detected, 2 of which were early stage and the patients had radical treatment. 5 pulmonary nodules were identified, for which interval follow-up was planned. Conclusion: The Northumbria Walk-in project proved successful in terms of delivering a campaign message to the local population. The trust communications team won a regional award for the best "low budget" campaign for this project. The detection rate for lung cancer was not higher than one would expect from performing CXR`s on a population of similar age with a smoking history and on current evidence did not provide evidence for continuing the walk in CXR programme. However, over the 2 years while this project was being developed and awareness of cancer was targeted there was a 6% rise in the rate of early stage lung cancer locally suggesting that the combined awareness raising approach both locally and nationally has had some effect on presentation rate.